Analisis Penyelesaian Soal Cerita Tipe HOTS Berdasarkan Kategori Kesalahan Watson - Teddy Septian R (PELITA JURNAL PENELITIAN DAN KARYA ILMIAH, 2022)
This study aims to identify and describe student's error on solving Higher Order Thinking Skills (HOTS) type of story problems based on Watson's error categories and their causes. The causes of student's mistakes are traced by referring to the modified didactic triangle, namely the Didactic Relationship (student-material), Pedagogical Relationship (student-teacher) and the Didactic-Pedagogical Anticipation Relationship (teacher-material). This study is a descriptive research especially case study with qualitative approach. Data collection was done by triangulation using test, interviews and documentation. The result of data analysis showed that all of Watson's error categories appeared in solving HOTS type of story problems. It caused by problems in Didactical Relationship, Pedagogical Relationship and Didactic-Pedagogical Anticipation Relationship.